CORRELATION BETWEEN STRESS LEVEL AND JUVENILE DELINQUENCY LEVEL IN STUDENTS OF SEKOLAH MENENGAH KEJURUAN 1 KURIPAN, WEST LOMBOK - Iyoega, Dara Asyfiya; Harahap, Herpan Syafii; Yudhanto, Didit; Pujiarohman, Pujiarohman (Universitas Muhammadiyah Malang, 2020)
ABSTRACTJuvenile delinquency is a kind of behavior that deviates from the norms prevailing in society. One factor that can affect the level of juvenile delinquency is stress. This study aimed to investigated the correlation between stress level and juvenile delinquency level in students of Sekolah Menegah Kejuruan (SMK) 1 Kuripan, West Lombok. This was cross-sectional involving 51 students of second and third-grade at Sekolah Menengah Kejuruan (SMK) 1 Kuripan, West Lombok. The data collected in this study were age, gender, stress level, and juvenile delinquency level. Stress level was measured using DASS-42 instrument, while juvenile delinquency level was measured using ASRDS instrument. The correlation between stress level and juvenile delinquency level was analyzed using Gamma correlation test and the correlation was significant if p<0.05. Most of the subjects showed mild stress levels (62%) and normal delinquency levels (78%).There was no significant correlation between stress levels and juvenile delinquency levels (p=0.076). In conclusion, stress level in students of SMK 1 Kuripan did not correlated to juvenile delinquency level.Keywords: Stress level, juvenile delinquency level, DASS-42 instrument, ASRDS instrument.